Y‐632 inhibits heat shock protein 90 (Hsp90) function by disrupting the interaction between Hsp90 and Hsp70/Hsp90 organizing protein, and exerts antitumor activity in vitro and in vivo. Issue 6 (27th April 2016) - Wang, Wenqian; Liu, Yang; Zhao, Zhixin; Xie, Chengying; Xu, Yongping; Hu, Youhong; Quan, Haitian; Lou, Liguang
Abstract : Heat shock protein 90 (Hsp90) stabilizes a variety of proteins required for cancer cell survival and has been identified as a promising drug target for cancer treatment. To date, several Hsp90 inhibitors have entered into clinical trials, but none has been approved for cancer therapy yet. Thus, exploring new Hsp90 inhibitors with novel mechanisms of action is urgent. In the present study, we show that Y‐632, a novel pyrimidine derivative, inhibited Hsp90 in a different way from the conventional Hsp90 inhibitor geldanamycin. Y‐632 induced degradation of diverse Hsp90 client proteins through the ubiquitin–proteasome pathway, as geldanamycin did; however, it neither directly bound to Hsp90 nor inhibited Hsp90 ATPase activity. Y‐632 inhibited Hsp90 function mainly through inducing intracellular thiol oxidation, which led to disruption of the Hsp90–Hsp70/Hsp90 organizing protein complex and further induced cell adhesion inhibition, G0 /G1 cell cycle arrest, and apoptosis. Moreover, Y‐632 efficiently overcame imatinib resistance mediated by Bcr‐Abl point mutations both in vitro and in vivo . We believe that Y‐632, acting as a novel small‐molecule inhibitor of the Hsp90–Hsp70/Hsp90 organizing protein complex, has great potential to be a promising Hsp90 inhibitor for cancer therapy, such as for imatinib‐resistant leukemia. Abstract : Y ‐632 is a promising Hsp90 inhibitor with novel mechanisms. Y ‐632 inhibits Hsp90 through disrupting Hsp90‐Hop interaction. Hsp90‐Hop interaction disruption results from Y ‐632 induced thiol oxidation.